Solidarity Economy and Mental Health: Issues and strategies for the social inclusion of people in mental suffering (Research, Society and Development, 2021)
The Psychiatric Reform movement in Brazil proposed the dismantling of the asylum model and the establishment of a new paradigm of mental health care, based on community treatment done in freedom and on proposals for social inclusion. The current national policy on Mental Health, known as the Psychosocial Care Network (RAPS), aims to promote and support its service’s users in their (re)insertion into work. In parallel, the Solidarity Economy presents itself as a means of material organization of life and work relationships based on the primacy of respect for human beings in their relationship with each other and with the environment, as well as on the ideals of cooperation, self-management and solidarity. At the same time, different initiatives to generate work and income based on the Solidarity Economy have been structured by different RAPS attention points, enabling new forms of social inclusion. In this scenario, the research in question consists of a systematic review with a qualitative approach, whose objective is to present the potentialities, challenges and strategies adopted in the literature to strengthen the interface between the fields of Mental Health and Solidarity Economy. The results suggest: the importance of the initiatives’ commitment to guarantee the right to work; the assisted workshops as the main strategy for the formation of enterprises; the lack of legal and public policy support for the constitution of the initiatives; as well as the lack of adequate spaces for commercialization and the low financial return to the enterprises.